Hubungan Kadar CA-125 Praoperatif terhadap Prognosis Survival Penderita Kanker Ovarium Epitelial di RSUP Dr.Sardjito - Pradjatmo, Herlina; Siswishanto, Rukmono; Prawitasari, Shinta (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: CA-125 level increases in 50% of patients with stage I, 90% of patients with stage II, 92% of patients with stage III and 94% of patients with stage IV ovarian cancer. CA-125 level were not a diagnostic tool to detect ovarian cancer, however it was useful to monitor the progressive of disease and as a prognostic marker.Objectives: The aim of this study is to prove whether CA-125 level before surgery in ovarian cancer patients at Dr. Sardjito Hospital as well as a factor that correlates to the survival prognosis of those patients.Method: This research used cohort retrospective study at Dr. Sardjito Hospital Yogyakarta.Result and Discussion: As much as 71 ovarian cancer patients which had been included in this research with inclusion and exclusion criteria. Subjects were divided into two groups. One group was for patients with low CA-125 level (≤35 U/ml) as much as 18 subjects and another group was for patients with high CA-125 level (>35 U/ml) as much as 53 subjects. The result of a bivariate analysis with an independent survival analysis (Cox’s Regression) was the stage of disease (p=0.005, HR 4.827, CI 95% 1.623 – 14.355) and residual tumour (p=0.029, HR 2.605, CI 95% 1.101 – 6.161) were a survival prognosis factor. Multivariate analysis with a survival analysis (Cox’s Regression) shows CA-125 level (p=0.031, HR 4.131, CI 95% 1.143 – 14.933) and menarche (p=0.003, HR 4.989, CI 95% 1.736 – 14.342) were significantly related with survival prognosis in EOC (Epithelial Ovarian Cancer) patients at Dr. Sardjito Hospital.Conclusion: CA-125 level affects the survival rate of epithelial ovarian cancer patients in Dr. Sardjito Hospital. Besides the level of CA-125, there are other factors that affect the survival rate of epithelial ovarian cancer patients which is the stage of cancer, residual operation and age of menarche.Keywords: CA-125 level, EOC, prognosis, survival.